PENGARUH KUALITAS LAPORAN KEUANGAN TERHADAP AKUNTABILITAS KINERJA INSTANSI PEMERINTAH (STUDI KASUS PADA BALAI BAHASA PROVINSI SUMATERA UTARA) - Sari, Ayu Permata; Nurlaila , Nurlaila (JAE (JURNAL AKUNTANSI DAN EKONOMI), 2022)
Abstract The purpose of this study was to determine the effect of the the quality of financial statements on the performance accountability of government agencies (a case study at the Language Center of North Sumatra Province). This type of research is causality. The data used are primary data and secondary data. Sampling is done by saturated sample or census. Data collection techniques using interview, questionnaire and documentation techniques. The analytical method used is simple linear regression. The result of this study indicate that the Quality ogf Financial Statements Agencies.